(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
The bony calvarium protects the most vital organ of our body.The skull is composed of various bones united by a zigzag line called sutures.The fusion of these sutures creates the protective calvarium of the brain.In addition to protection, this suture line helps during parturition. When the anterior and posterior fontanelle attaches via a fibrous sheet, it has a favorable shape during vaginal delivery and helps in the development of the brain.The suture fuses with the adjacent bones at certain ages and creates a protective calvarium.During this period, suture diastasis occurs due to various causes, such as RTA, falls, and increased intracranial pressure.It is usually associated with an additional fracture line; however, under